Rats' choices with token stimuli in concurrent variable- interval schedules - Mazur, James E. (Journal of the Experimental Analysis of Behavior, 2014)
Four rats responded on concurrent variable-interval schedules that delivered token stimuli (stimulus lights arranged vertically above each of two side levers). During exchange periods, each token could be exchanged for one food pellet by responding on a center lever, with one response required for each pellet delivery. In different conditions, the exchange requirements (number of tokens that had to be earned before they could be exchanged for food) varied between one and four for the two response levers. The experiments were closely patterned after research with pigeons by Mazur and Biondi (), and the results from the rats in the present experiment were similar. Response percentages on the two levers changed as each additional token was earned, and these patterns indicated that choice was controlled by both the time to the exchange periods and the number of food pellets that were delivered in the exchange period. In some conditions, the exchange requirement was three tokens for each lever, but the token lights were not turned on as they were earned for one of the two keys. The rats showed a slight preference for the lever without the token lights, which may indicate that the token lights were not serving as conditioned reinforcers (a result also found by Mazur and Biondi with pigeons). Overall, these results suggest that, in this choice procedure, the token stimuli served primarily as discriminative stimuli that signaled the temporal proximity and quantity of the primary reinforcer, food.
0 citations (Crossref) [2023-10-31] tex.eissn: 1938-3711 tex.researcherid-numbers: Mazur, James/AAA-6971-2019 tex.unique-id: ISI:000341714000004
Keywords: Animals; Choice Behavior; Concurrent variable-interval schedules; Conditioned reinforcers; Conditioning; Operant; Cues; Discriminative stimuli; Hyperbolic discounting; Lever press; Long Evans rat; Male; Rats; Rats; Long-Evans; Reinforcement Schedule; Token Economy; Token stimuli; animal; association; decision making; dept.psy; instrumental conditioning; male; peer-reviewed; rat; reinforcement